Mirabegron elicits rat corpus cavernosum relaxation and increases in vivo erectile response - de Oliveira, Mariana G.; Rojas-Moscoso, Julio Alejandro; Bertollotto, Gabriela M.; Candido, Tuany Z.; Kiguti, Luiz Ricardo de A.; Pupo, André S. [UNESP]; Antunes, Edson; De Nucci, Gilberto; Mónica, Fabíola Z. (Elsevier, 2019)
Mirabegron is the first β3-adrenoceptor agonist approved on the market and may offer beneficial pharmacological action in patients with overactive bladder and erectile dysfunction. Here, we further investigate the mechanisms by which mirabegron induces rat corpus cavernosum (CC) relaxation. Adult male Wistar rats were used. The CC were isolated for in vitro functional assays and β-adrenoceptors subtypes mRNA expression evaluation. Animals were treated orally with mirabegron (30 mg/kg, 3 h), tadalafil (10 mg/kg, 3 h) or both for intracavernous pressure (ICP). Intracellular levels of cAMP and cGMP were also determined. The β1-, β2- and β3-adrenoceptors subtypes were expressed in rat CC. Mirabegron produced concentration-dependent CC relaxations that were unaffected by the β1-, β2- or β3-adrenoceptor antagonists atenolol (1 μM), ICI-118,551 (1 μM) and L748,337 (10 μM), respectively. Mirabegron-induced relaxations were not affected by the phosphodiesterase type 4 inhibitor, rolipram, or the adenylyl cyclase selective inhibitor, SQ 22,536. Potassium channel- or calcium influx-blockade are not involved in mirabegron-induced relaxations. In contrast, mirabegron produced rightward shifts in the contractile response induced by the α1-adrenoceptor agonist, phenylephrine. Finally, cavernous nerve stimulation caused frequency-dependent ICP increases, which were significantly increased in rats treated with mirabegron in a similar degree of tadalafil-treated rat, without promoting a significant cAMP or cGMP accumulation. Together, our results demonstrate that mirabegron induced CC relaxation through α1-adrenoceptor blockade. Care should be taken to translate the effect of mirabegron into the clinic, especially when using rat as an animal model of erectile dysfunction.
Keywords: Cyclic AMP; Cyclic GMP; Erectile dysfunction; Intracavernous pressure; Mirabegron; Tadalafil